The effects of rTMS on impulsivity in normal adults: a systematic review and meta-analysis - Yang, Cheng-Chang; Völlm, Birgit; Khalifa, Najat (Springer, 2018)
Background: Impulsivity is a multi-dimensional construct that is regarded as a symptom of many psychiatric disorders. Harm resulting from impulsive behaviour can be substantial for the individuals concerned, people around them and the society they live in. Therefore, the importance of developing therapeutic interventions to target impulsivity is paramount. Aims and methods: We conducted a systematic review and meta-analysis of the literature from AMED, Embase, Medline, and PsycINFO databases on the use of repetitive transcranial magnetic stimulation (rTMS) in healthy adults to modulate different subdomains (motor, temporal and reflection) of impulsivity. Results: The results indicated that rTMS has distinct effects on different impulsivity subdomains. It has a significant, albeit small, effect on modulating motor impulsivity (g = 0.30, 95% CI, 0.17 to 0.43, p < .001) and a moderate effect on temporal impulsivity (g = 0.59, 95% CI, 0.32 to 0.86, p < .001). Subgroup analyses (e.g., excitatory vs. inhibitory rTMS, conventional rTMS vs. theta burst stimulation, analyses by stimulation sites, and type of outcome measure used) identified key parameters associated with the effects of rTMS on motor and temporal impulsivity. Age, sex, stimulation intensity and the number of pulses were not significant moderators for effects of rTMS on motor impulsivity. Due to lack of sufficient data to inform a meta-analysis, it has not been possible to assess the effects of rTMS on reflection impulsivity. Conclusions: The present findings provide preliminary evidence that rTMS can be used to modulate motor and temporal impulsivity in healthy individuals. Further studies are required to extend the use of rTMS to modulate impulsivity in those at most risk of engaging in harmful behaviour as a result of impulsivity, such as patients with offending histories and those with a history of self-harming behaviour.